PLANNING A SUSTAINABLE TOURISM DESTINATION FOCUSING ON TOURISTS’ EXPECTATIONS, PERCEPTIONS AND EXPERIENCES - Anna KYRIAKAKI; Maria KLEINAKI (Geo Journal of Tourism and Geosites, 2022)
This study aims to research the special characteristics, expectations and experiences of the tourists a destination attracts and elaborate them during sustainable tourism planning in the effort to (re)build a destination. Research conducted in southern Chania, Crete, Greece based a) on a structured questionnaire to capture the characteristics of tourists visiting the area, their motivation and opinions b) a content analysis of the material posted on “Trip Advisor” in order to understand the perceived image of the area. Cluster analysis highlighted three groups a) the eternal lovers, b) the devoted families and c) the adventurers. All groups declared a high degree of satisfaction and loyalty to the destination and a strong interest in sustainable and alternative tourism. Nevertheless, the commercial image of the area continues to focus on the model "Sun - Sea - Sand", without sufficiently highlighting other local resources. The results can be the basis for the enrichment and upgrading of the quality of the existing tourism product, to be supported by a management model under the UN SDGs. This approach is expected to increase the competitiveness of the destination and lead to sustainable development.